Free to obey how the Nazis invented modern management - Chapoutot, Johann 1978- (Europa Editions, 2023)
Reinhard Höhn (1904-2000) was a commander of the SS, one of Nazi Germany's most brilliant legal minds, and an archetype of the fervid technocrats and intellectuals that built the Third Reich. Following Germany's defeat, after a few years in hiding, he emerged in the early 1950s as the founder and director of a renowned management school in Lower Saxony. Höhn's story wouldn't be very different from that of many other prominent Nazis if not for the fact that a vast number of Germany's postwar business leaders--more than 600,000 executives--were educated at his management school. In this fascinating book, Johann Chapoutot, one of France's most brilliant historians, traces the profound links between Nazism and the principles of modern corporate management, our definitions of success, and a concept of personal freedom that masks rigid hierarchical structures of power and control
Keywords: Höhn, Reinhard -- 1904-2000; Akademie für Führungskräfte der Wirtschaft; Geschichte; Ausbildung; Management; Nachkriegszeit; Niedersachsen; Höhn, Reinhard / 1904-2000; National socialism; Management / History; Germany / History; HISTORY / Europe / Germany; Germany; History